The first step in problem

  1. A student solves the following problem:Problem: 2(x - 3) + 3x = 19 Step 1: 2x - 6 + 3x = 19 Step 2: (2x + 3x) - 6 = 19 Step 3:
    1. answers icon 1 answer
    2. views icon 24 views
  2. A student solves the following problem:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
    2. views icon 17 views
  3. A student solves the following problem:Problem: 2(x−3) + 3x = 19 Step 1: 2x − 6 + 3x = 19 Step2: (2x + 3x) −6 = 19 Step 3:
    1. answers icon 1 answer
    2. views icon 132 views
  4. A student solves the following problem:Problem: 2(x-3) + 3x = 19 Step 1: 2x - 6 + 3x = 19 Step2: (2x + 3x) -6 = 19 Step 3: 5х -
    1. answers icon 1 answer
    2. views icon 75 views
  5. A student solves the following problem:Problem: 2(x−3) + 3x = 19 Step 1: 2x − 6 + 3x = 19 Step2: (2x + 3x) −6 = 19 Step 3:
    1. answers icon 1 answer
    2. views icon 79 views
  6. Question 1 A) A student solves the following problem: Problem: 2(x−3)+3x=192(x−3)+3x=19 Step 1: 2x−6+3x=192x−6+3x=19
    1. answers icon 7 answers
    2. r asked by r
    3. views icon 33 views
  7. A student solves the following problem:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step2: (2x+3x)−6=19 Step 3: 5x−6=19 Step
    1. answers icon 1 answer
    2. views icon 30 views
  8. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 43 answers
    2. Kappa asked by Kappa
    3. views icon 399 views
  9. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
    2. views icon 118 views
  10. A student solves the following equation:Problem: 2(x−3)+3x=19 Step 1: 2x−6+3x=19 Step 2: (2x+3x)−6=19 Step 3: 5x−6=19
    1. answers icon 1 answer
    2. myworldwha asked by myworldwha
    3. views icon 30 views